Upgrading of Napier grass pyrolytic oil using microporous and hierarchical mesoporous zeolites: Products distribution, composition and reaction pathways - Mohammed, I.Y. (Elsevier Ltd, 2017)
Reaction pathways in ex-situ catalytic upgrading of pyrolytic oil towards formation of specific products such as hydrocarbons are still not well established due to the presence of many different organic components in the raw pyrolytic oil. Currently, only a few studies are available in literature particularly with regards to application of hierarchical mesoporous zeolite in the refinement of sample pyrolytic oil. This study provides the first experimental investigation of ex-situ catalytic upgrading of pyrolytic oil derived from Napier grass using microporous and hierarchical mesoporous zeolites. Two hierarchical mesoporous zeolites were synthesized by desilication of microporous zeolite using 0.2 and 0.3 M solution of sodium hydroxide. Upgrading over microporous zeolite produced 16.0 wt solid, 27.2 wt organic phase and 23.9 wt aqueous phase liquid while modified zeolites produced 21–42 less solid and 15–16 higher organic phase liquid. Higher degree of deoxygenation of pyrolytic oil was achieved with the modified zeolites. Analysis of organic phase collected after catalytic upgrading revealed high transformation of oxygenates into valuable products. Bulk zeolite produced cyclic olefins and polyaromatic hydrocarbons while mesoporous zeolites were selective toward cycloalkanes and alkylated monoaromatic production, with significant reduction in the production of polyaromatic hydrocarbon. Result of gas analysis showed that hierarchical mesoporous zeolite favored decarboxylation and decarbonylation reactions compared to the parent zeolite, which promoted dehydration reaction. Mesoporous zeolite produced with 0.3 M sodium hydroxide solution was found to be the best-performing catalyst and its reusability was tested over four consecutive cycles. This study demonstrated that pyrolytic oil derived from Napier grass can be transformed into high-grade oil over hierarchical mesoporous zeolite. © 2017 Elsevier Ltd